Avaliação da influência do remanescente de hidróxido de cálcio na infiltração marginal de dentes tratados endodonticamente - Oliveira, Maria Antonieta Veloso Carvalho de (2010)
The presence of calcium hydroxide intracanal medicament residual even after its clinical removal, regardless of the technique or material used, is a fact proven by the literature. The aim of this study was to evaluate the influence of remaining Ca(OH)2 on marginal leakage of endodontic treated teeth. Two levels of leakage were considered: through apical foramen and root s medium third and the dye diffusion was quantified in length and depth. Seventy-two single-rooted bovine teeth after root canal biomechanical preparation were divided into two groups GI and GII (n=36). Specimens of the GI group, after canal preparation were immediately obturated and the GII samples were filled with Ca(OH)2 associated with saline solution. After seven days the medication was removed and the canals were filled likewise GI group by lateral condensation technique with a zinc oxide-eugenol sealer. Half of the specimens of GI and GII (n = 18) had their apical third and part of the medium third removed and alongside with the full-length roots , were immersed in India ink for 72 hours. For the evaluation of dye leakage the experimental specimens were cross-sectioned, photographed and had the infiltration perimeter measured by means of the Image Tool 3.00 software. After the analysis of length and depth infiltration, the lowest dye penetration values were found in Ca(OH)2 medicament receiving groups, independently of the leakage level. Therefore, we concluded that the use of Ca(OH)2 intracanal medicament significantly decrease the dye leakage through both apical foramen and root s medium third regarding length and depth.